2005
DOI: 10.1007/s11262-004-4589-6
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Cellular Proteins to the Leader RNA of Equine Arteritis Virus

Abstract: The genome of equine arteritis virus (EAV) produces a 3' coterminal-nested set of six subgenomic (sg) viral RNAs during virus replication cycle, and each set possesses a common leader sequence of 206 nucleotides (nt) in length derived from the 5' end of the viral genome. Given the presence of the leader region within both genomic and sg mRNAs, it is likely to contain cis-acting signals that may interact with cellular or viral proteins for RNA synthesis. Gel mobility shift assays indicated that proteins in Vero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
(22 reference statements)
1
2
0
Order By: Relevance
“…Cellular proteins appeared to bind to similar regions in the antileader of other arteriviruses including EAV, an observation that we recently confirmed [25]. In addition, we also observed cellular proteins to bind to the EAV leader RNA positive strand and showed that nt 140-206 are not necessary for this binding.…”
Section: Discussionsupporting
confidence: 83%
“…Cellular proteins appeared to bind to similar regions in the antileader of other arteriviruses including EAV, an observation that we recently confirmed [25]. In addition, we also observed cellular proteins to bind to the EAV leader RNA positive strand and showed that nt 140-206 are not necessary for this binding.…”
Section: Discussionsupporting
confidence: 83%
“…For arteriviruses, the common leader sequence of EAV sub-genomic viral RNAs, too, possesses the ability to interact several cellular proteins from the cytoplasmic fractions of Vero cells, likely for the modulation of EAV RNA synthesis [ 172 ].…”
Section: Cellular Factors Involved In the Virus Life Cyclementioning
confidence: 99%
“…6 Although thousands of articles have been published regarding the role of apoptosis in physiologic and pathologic processes in various species, there is a paucity of information regarding apoptosis in horses. To date, publications concerning apoptosis in horses have been limited to aspects of reproductive physiology, [7][8][9] exercise physiology, 10 chondrocyte growth, 11 virus infection, [12][13][14][15][16] melanocytic tumors, 17 and gastrointestinal tract disease. 18,19 To the authors' knowledge, there are no reports regarding apoptosis in the laminae of healthy horses or horses with laminitis.…”
Section: Conclusion and Clinicalmentioning
confidence: 99%